IN VITRO REGENERATION OF POTATO (Solanum tuberosum L.) - Molla, M. M. H.; Nasiruddin, K. M.; Al-Amin, M.; Haque, M. S.; Khanam, D. (Bangladesh Journal of Plant Breeding and Genetics, 2011)
The experiment was conducted during the period from January to December, 2008 at the Laboratory of Biotechnology, Bangladesh Agricultural Research Institute, Gazipur, Bangladesh. A two step procedure was followed for direct plant regeneration of potato. Murashige and Skoog (MS) basal medium supplemented with 0.5 mg l-1 IBA and 30 g sugar was used for in vitro potato plants development via nodal cuttings. Leaves and internodes of in vitro grown potato variety Asterix was cultured in instant MS basal medium supplemented with 0.01 mg l-1 IAA, 0.20 mg l-1 GA3, 44.0 g l-1 CaCl2, 20 g sucrose. Eight different concentrations of Zeatin riboside (ZR) viz., 0, 0.1, 1.0, 2.0, 3.0, 4.0, 5.0, 6.0 mg l-1 along with above supplements (step II) were tested for in vitro direct regeneration of potato. MS medium supplemented with 4-5 mg l-1 of ZR performed better in respect of shoot induction from internodal explants. All the internodes produced shoots directly from the basal and apex region within 18-21 days and from the leaves within 21-28 days in 2 - 5 mg l-1 ZR. Maximum 43.20 and 7.25 shoots were recorded from each internode and leaf explant, respectively. In vitro shoots treated with 0.5 mg l-1 of IBA produced roots profusely within 21 days. DOI: http://dx.doi.org/10.3329/bjpbg.v24i1.16307